2007
DOI: 10.1186/1472-6963-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Indian community health insurance schemes provide partial protection against catastrophic health expenditure

Abstract: BackgroundMore than 72% of health expenditure in India is financed by individual households at the time of illness through out-of-pocket payments. This is a highly regressive way of financing health care and sometimes leads to impoverishment. Health insurance is recommended as a measure to protect households from such catastrophic health expenditure (CHE). We studied two Indian community health insurance (CHI) schemes, ACCORD and SEWA, to determine whether insured households are protected from CHE.MethodsACCOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 21 publications
3
95
1
Order By: Relevance
“…Results pertaining to financial protection are also ambiguous. While several studies have found positive impacts of CBHI on financial protection (Bennett et al, 1998, Ekman, 2004ILO, 2002), most of them (Devadasan et al, 2007;Baeza et al, 2002;Jowett, 2002;Ju¨tting, 2004) suggest that protection has been only marginal. Ranson (2001) finds no evidence of an effective protection effection.…”
Section: Health and Economic Outcomes: Major Hypotheses And Empiricalmentioning
confidence: 95%
“…Results pertaining to financial protection are also ambiguous. While several studies have found positive impacts of CBHI on financial protection (Bennett et al, 1998, Ekman, 2004ILO, 2002), most of them (Devadasan et al, 2007;Baeza et al, 2002;Jowett, 2002;Ju¨tting, 2004) suggest that protection has been only marginal. Ranson (2001) finds no evidence of an effective protection effection.…”
Section: Health and Economic Outcomes: Major Hypotheses And Empiricalmentioning
confidence: 95%
“…This approach is considered as a highly regressive way of financing healthcare which sometimes leads to impoverishment. 9 Of course, who really pays for the healthcare services surely affects the percentage of impoverished households. 5 In the recent years, several reports have been published on CHE in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The health financing mechanism was developed to counteract the detrimental effects of user fees introduced in the 1980s, which now appear to inhibit heath care utilization, particularly for marginalized populations, and to sometimes lead to catastrophic health expenditures. [1][2][3] The World Health Organization (WHO) considers health insurance a promising means for achieving universal health-care coverage. 4 Various types of health insurance are available.…”
Section: Introductionmentioning
confidence: 99%